Impact of social media addiction on physical activity among undergraduate students - Mak, Kai Nan (2022)
Background and Objective: The study aims to find the impact of social media addiction on physical activity level among undergraduate students in UTAR. Through the evolution of Internet technologies, there is a surge in excessive use of social media. An individual who misuses social media may lead to social media addiction, hence negatively affected health physically and mentally. The objective of this study was: to find out the impact of social media addiction on physical activity level among undergraduate students in UTAR. Methods: A total of 378 undergraduate students from different faculty or department of UTAR Sungai Long and Kampar campus were involved in this crosssectional study. The online questionnaire was randomly disseminated to students from all faculties through social media. Participants were also recruited around the campus by providing the QR code to be scanned. Results: There is no significant associations between social media addiction and physical activity level. More than half of the subjects were observed to be suffering from social media addiction (n = 353, 93.4%). Majority of the participants reported moderate physical activity levels (n = 161, 42.6%). Conclusions: No significant associations between social media addiction and physical activity level. A significant number of subjects reported to have social media addiction. Awareness campaign or education through multimedia information should be encouraged in the institution as well as the community in order to improve the alertness of individual regarding social media addiction.